Transcatheter versus surgical aortic valve replacement in patients with aortic stenosis: characterization of molecular pathways before and after treatment. (10th June 2022) - Bonanni, A; Pedicino, D; D'aiello, A; Vinci, R; Severino, A; Russo, G; Cribari, F; Conte, C; Filomia, S; Bruno, P; Burzotta, F; Trani, C; et al.
Abstract: Funding Acknowledgements: Type of funding sources: None. Background/Introduction: Recently, the transcatheter aortic valve replacement (TAVR) has reformed the management of Aortic Stenosis (AS), providing a valid therapeutic alternative to surgical aortic valve replacement (SAVR). Although optimizing the timing of surgery is a crucial aspiration, the introduction of innovative pharmacological therapies able to modify disease evolution might help clinicians to treat patients in a non-invasive way. Several evidences pointed out the role of inflammation, oxidative stress, and pathological remodelling in AS natural history. Purpose: The aim of this study is to assess biological pathways modifications after aortic valve replacement, comparing the transcatheter and the surgical approach. Methods: We enrolled a total of 35 consecutive patients with severe symptomatic aortic stenosis undergoing aortic valve replacement with transcatheter (n = 19) or surgical (n = 16) approach. Biological samples were collected and stored before (T0) and 72 hours after the procedure (T1). We firstly performed gene expression arrays for a total of 132 genes, on two groups of pooled cDNA from peripheral blood mononuclear cells of TAVR (n = 10) and SAVR (n = 10) patients. Then, taking into account the most relevant result of the arrays, we selected 15 genes for validation. Results: Our preliminary data showed several differences in the gene expression levels of the two groups under examination for a large number of molecules, mostly associated with the oxidative balance. More in detail, after procedure, TAVR patients showed higher levels of glutathione peroxidase 1 (GPX1, TAVR p = 0.029; SAVR p = 0.031) and glutathione reductase (GSR, p = 0.029), while SAVR patients showed higher expression of GPX1, catalase (CAT, p = 0.019) and NADPH oxidase 2 (NOX2, p = 0.008), thus confirming an intense post-operative oxidative stress particularly for patients undergoing surgery. Moreover, Caspase 3 (CASP3, p = 0.013), involved in apoptotic pathway and myocyte enhancer factor 2C (MEF2C, p = 0.036), implicated in overload induced hypertrophy genes showed a significantly reduction in their expression after TAVR. Conclusions: In our study, we describe different gene expression signatures in patients with an AS diagnosis and their recalibration after AV replacement with two kinds of procedure, TAVR and SAVR. Our data describe for the first time an altered oxidative balance in patient undergoing aortic valve replacement, that is particularly evident for patients undergoing SAVR. A clearer understanding of biological processes taking place in the first hours post AV replacement lays the ground to a more efficient management of post-operative status and, in the incessant research for a tailored therapy, the results of our study add a little piece of information to assist clinicians in selecting the optimal procedure for each patient.